Pengaruh Kualitas Produk, Fitur Produk dan Desain Produk Terhadap Keputusan Pembelian Produk Kosmetik Dalam Perspektif Manajemen Islam - Lestari, Devi; Asriani, Asriani; Ningsih, Nur Wahyu; Rosilawati, Weny; Amrina, Dania Hellin (REVENUE: Jurnal Manajemen Bisnis Islam, 2022)
In the times and technology makes business competition more advanced. It becomes an opportunity to introduce and maintain the product. The number of similar products makes a strategy to make it easier for consumers to choose the product they are looking for. With the development of consumers, consumer desires also develop where the purchase of a product is no longer a need but also a desire. The desire of consumers is not only to meet basic needs but also to problems with physical appearance, especially on the face, which is a beauty that is a top priority for users. The formulation of the problem in this research is whether product quality, product features, product design have a positive and significant effect on purchasing decisions? Then do product quality, product features, product design have a positive and significant effect on purchasing decisions for cosmetic products at the Kartika Aesthetic Beauty Clinic and Erha Bandar Lampung Beauty Clinic in an Islamic management perspective? This study aims to determine the effect of product quality, product features and product design on purchasing decisions for cosmetic products and to describe it in an Islamic management perspective.      This research uses descriptive quantitative method, which is a research method to examine a particular population or sample in order to test the hypothesis that has been set. The data collection techniques in the form of questionnaires and interviews. Sampling in this study by taking the Accidental Sampling technique. And this data collection method using a questionnaire given to 100 respondents each of 50 respondents and interviews with the Beauty Clinic.      The results of this test indicate that product quality has a positive and significant effect on purchasing decisions at the Kartika Aesthetic Beauty Clinic with a significant value of 0.014 <0.05 and the Erha Beauty Clinic with a significant value of 0.025 <0.05. Meanwhile, the product features at the Kartika Aesthetic Beauty Clinic with a significant value of 0.030 <0.05 and the Erha Beauty Clinic with a significant value of 0.011 with a significant value <0.05. As well as product design at the Kartika Aesthetic Beauty Clinic with a significant value of 0.034 <0.05 and the Erha Beauty Clinic with a significant value of 0.017 <0.05. Based on data analysis, the conclusion of product quality, product features, and product design affects the purchasing decisions of cosmetic products at the Kartika Aesthetic Beauty Clinic and Erha Beauty Clinic in Bandar Lampung from an Islamic management perspective.